2008
DOI: 10.1080/10683160801950523
|View full text |Cite
|
Sign up to set email alerts
|

Sex offenders’ perceptions of the effectiveness and fairness of humanity, dominance, and displaying an understanding of cognitive distortions in police interviews: A vignette study

Abstract: Forty-three convicted sex offenders read each of four different offence vignettes that involved a man forcing a female victim into sex and the offender's subsequent police interview. The experimental manipulation involved giving participants each of four different scenarios concerning how the police interviewed the offender. These were interviews characterized by humanity, dominance, displaying an understanding of sex offenders' cognitive distortions, or a neutral, control interview. Participants were required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 31 publications
2
32
0
2
Order By: Relevance
“…The conclusion, at least in the present sample, is that across all three offence types, the use of appropriate question types appears to be more beneficial in eliciting a greater amount of relevant information than the use of empathy per se. Although research in this area is limited, there are two distinct strands emerging, with some focusing on either the offenders' perspective of the interview process (Holmberg & Christianson, 2002;Kebbell et al, 2006), the obtaining of confessions (Beauregard, Deslauriers-Varin, & St-Yves, 2010;Kebbell, Alison & Hurren, 2008), or both. The present authors would argue that, in line with the principles of ethical interviewing, the primary goal of an investigative interview is not to obtain a confession per se, rather, it is to obtain accurate, relevant and complete accounts to provide the investigation team with relevant information to enable them to proceed with their enquiry (Milne & Bull, 1999;Williamson, 1993).…”
Section: Discussionmentioning
confidence: 98%
“…The conclusion, at least in the present sample, is that across all three offence types, the use of appropriate question types appears to be more beneficial in eliciting a greater amount of relevant information than the use of empathy per se. Although research in this area is limited, there are two distinct strands emerging, with some focusing on either the offenders' perspective of the interview process (Holmberg & Christianson, 2002;Kebbell et al, 2006), the obtaining of confessions (Beauregard, Deslauriers-Varin, & St-Yves, 2010;Kebbell, Alison & Hurren, 2008), or both. The present authors would argue that, in line with the principles of ethical interviewing, the primary goal of an investigative interview is not to obtain a confession per se, rather, it is to obtain accurate, relevant and complete accounts to provide the investigation team with relevant information to enable them to proceed with their enquiry (Milne & Bull, 1999;Williamson, 1993).…”
Section: Discussionmentioning
confidence: 98%
“…Research relating to interviews with suspected sex offenders is still very much in its infancy and the research that has been conducted has tended to focus upon the offenders' perspective of the interview process (Holmberg & Christianson, 2002;Kebbell et al, 2006;Kebbell, Alison, & Hurren, 2008), with very little being conducted on real-life interviews of offenders (but see Benneworth, 2007;Oxburgh et al, 2006). To our knowledge, the present study is the first that has used transcripts of actual interviews to examine whether empathy impacts on the amount of IRI obtained in interviews with suspected child sex offenders.…”
Section: Discussionmentioning
confidence: 99%
“…Interviews with 83 convicted offenders in Sweden and written surveys of 63 convicted sex and violent offenders in Australia revealed that detainees who were interrogated by interviewers whom they perceived to be empathetic and humane confessed to their crimes, whereas detainees who did not confess perceived their interviewer as more authoritarian, domineering, accusatory and judgmental (Holmberg & Christianson, ; Kebbell, Alison, Hurren, & Mazzerolle, ). Results of a written vignette study completed by 43 sex offenders indicated that when the interview style portrayed was procedurally fair and human, they perceived confessions as more likely than when it was procedurally unfair and domineering (Kebbell, Alison, & Hurren, ).…”
Section: Coercive Versus Noncoercive Interview Strategiesmentioning
confidence: 99%